2019
DOI: 10.3390/ijms20204982
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β3/Chitosan Sponge (TGF-β3/CS) Facilitates Osteogenic Differentiation of Human Periodontal Ligament Stem Cells

Abstract: Periodontal disease is the main reason for tooth loss in adults. Tissue engineering and regenerative medicine are advanced technologies used to manage soft and hard tissue defects caused by periodontal disease. We developed a transforming growth factor-β3/chitosan sponge (TGF-β3/CS) to repair periodontal soft and hard tissue defects. We investigated the proliferation and osteogenic differentiation behaviors of primary human periodontal ligament stem cells (hPDLSCs) to determine the bioactivity and potential ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 49 publications
(50 reference statements)
1
13
0
Order By: Relevance
“…However, the CS-P experimental group exhibited a statistically significant difference with respect to the control group (p < 0.0001), which presented lower cell viability. This result is in accordance with previous studies, which observed an increase of viable cells in different linage cells when chitosan was used as a biomaterial base [63][64][65]. The rates of cell viability exhibited by both groups make them suitable for biomedical use according to the International Organization for Standardization (ISO) and the national standards for Biological Evaluation of Medical Devices, ISO 10993-5 [66].…”
Section: Biological Analysissupporting
confidence: 91%
“…However, the CS-P experimental group exhibited a statistically significant difference with respect to the control group (p < 0.0001), which presented lower cell viability. This result is in accordance with previous studies, which observed an increase of viable cells in different linage cells when chitosan was used as a biomaterial base [63][64][65]. The rates of cell viability exhibited by both groups make them suitable for biomedical use according to the International Organization for Standardization (ISO) and the national standards for Biological Evaluation of Medical Devices, ISO 10993-5 [66].…”
Section: Biological Analysissupporting
confidence: 91%
“…It is reported that Sp7 is a transcription factor for osteoblast differentiation, whereas Runx2 is known as a downstream gene ( Xin et al, 2019 ). BMP2 pathway is known to up-regulate Sp7 expression through two distinct transcription factors such as Runx2 and Msx2 during osteoblast differentiation ( Li et al, 2019 ; Tang et al, 2019 ). Accumulating data proved that BMP2 is involved in bone formation, bone remodeling, bone development, and osteoblast differentiation through hBMSC osteogenic differentiation ( Biswas et al, 2018 ; Wu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β3 induces endochondral bone formation and completes bone remodeling. The signal transduction mediated by TGF-β 3 in osteogenic differentiation and bone regeneration specifically occurs through both canonical SMAD -dependent pathways with TGF-β3 ligands, receptors, and SMADs ( Li et al, 2019 ). Indeed, TGFβ3 gene and SMAD3 transcription factor up-regulation could induce bone regeneration by amplifying hBMSCs recruitment at the damaged site ( Deng et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that Sp7 is a transcription factor for osteoblast differentiation, whereas Runx2 is known as a downstream gene (Xin et al, 2019). BMP2 pathway is known to upregulate Sp7 expression through two distinct transcription factors such as Runx2 and Msx2 during osteoblast differentiation (Li et al, 2019;Tang et al, 2019). Accumulating data proved that BMP2 is involved in bone formation, bone remodeling, bone development, and osteoblast differentiation through hBMSC osteogenic differentiation (Biswas et al, 2018;Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β3 induces endochondral bone formation and completes bone remodeling. The signal transduction mediated by TGF-β 3 in osteogenic differentiation and bone regeneration specifically occurs through both canonical SMAD-dependent pathways with TGF-β3 ligands, receptors, and SMADs (Li et al, 2019). Indeed, TGFβ3 gene and SMAD3 transcription factor up-regulation could induce bone regeneration by amplifying hBMSCs recruitment at the damaged site (Deng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%